Effect of metaldehyde, botanical extracts, and common salt on gastropod (Sarasinula plebeia) of common beans (Phaseolus vulgaris) voluble var. “Rojo Bolón” in two growth cycles - Bolanos Carriel, Carlos (2025)
Common bean (Phaseolus vulgaris) is an important source of protein worldwide. The gastropod Sarasinula plebeia is troublesome pest that can cause serious damage. This study evaluated the effectiveness of chemical, physical, and botanical control methods against S. pleabeia in common bean. Four treatments were applied: metaldehyde (0.5 g/plant and 1 g/plant), rue and rosemary extract, and common salt, using a randomized complete block design (RCBD) with four replications over two growing seasons (2023 and 2024). A repeated measures model was used, and the Toeplitz structure provided the best fit to the data (AIC = 2,452.95; BIC = 2,491.58). The treatments showed significant differences (p < 0.0001), with metaldehyde being the most effective. Although botanical and physical controls also reduced gastropod populations, the botanical extract was more effective than physical in 2023. The study concludes that an integrated management strategy combining different control methods is more effective in reducing S. plebeia populations and minimizing crop damage, especially under reduced tillage systems.